PENGEMBANGAN AGROWISATA BERLANDASKAN KONSEP TRI HITA KARANA DI SUBAK UMA LAMBING, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Ni Luh Putu Erma Mertaningrum; Wayan - Windia; Ratna Komala Dewi (JURNAL MANAJEMEN AGRIBISNIS, 2019)
ABSTRACT In an effort to agro-tourism development at Subak Uma Lambing, it is necessary to analyze the potential, form of development, and suitability between the ideal situation and the actual situation of subak. Based on that, it is necessary to do analysis based on the concept of Tri Hita Karana. The purpose of this study is to analyze the potential, the form of agro-tourism development, and the suitability between the ideal situation and the actual situation at Subak Uma Lambing related to the agro-tourism development based on Tri Hita Karana concept. This research used pekaseh and tourism actors as a main informant, and the member of subak as respondent. Methods and techniques of data collection used are observation, in-depth interviews, questionaires, documentation, and triangulation. Data analysis methods and techniques used are qualitative descriptive analysis, and matrices analysis of relationships between technology sub-systems and cultural sub- systems. The results showed that Subak Uma Lambing has the potential of tourist attraction, transportation type, electricity flow and lighting. Roads, parking lots, health facilities, food and beverage kiosks, souvenir shops, lodging, and accessibility based on distance and ease with other tourist locations. Agro-tourism is developed using an mindset aspect, social aspect, and artifacts aspect with alternative forms of agro-tourism is tracking, jogging, cycling, metekap, nandur, manyi, feeding cows, feeding fish, fishing trips, fruits and vegetables picking tours, studying rindic instruments, watching ritual activities, enjoy typical Balinese food, mejejahitan, capil wraping, traditional games, entertainment Balinese Dance and stay at krama subak home. In general, the application of the concept of Tri Hita Karana approaching the ideal situation, but on the relationship of social sub-system with sub-organoware system has not reached the ideal. In this study, it is advisable to maintain the cleanliness of irrigation channels, as well as to improve and equip facilit ies and infrastructure. An agreement needs to be made on manners, local government and tourism bureaus, collaboration between subak institution and krama to realizing the artifact aspects.